Pengaruh Iradiasi Sinar Gamma Pada Benih Terhadap Keragaan Tanaman Jengger Ayam (Celosia cristata L.) - Maria Afnita Lelang; Adi Setiadi; Fitria . (Savana Cendana, 2016)
Study the effect of gamma irradiation on the performance of the plant seed from the chicken's comb (Celosia cristata L.) aims to Obtain mutant plants Celosia unique, interesting, and stable that can be used as a lucrative new varieties on the market. Getting a mutant plant that has the highest diversity in LD50. The experiment was conducted in February 2013 to April 2013. This research was conducted at the Nuclear Energy Agency (BATAN) Pasar Minggu and Development Center of Ornamental Plants Bogor Agricultural Institute (IPB), Taman Kencana, Bogor. This study uses Celosia seeds irradiated with various doses. The dose used is: 0 Gy, 10 Gy, 20 Gy, 30 Gy, 40 Gy, 50 Gy. Observations were made on the Reduction parameter Dose (RD) 50, High Plant (cm), Number Buds (buds), Flower color and Form Flowers. The results showed that the highest dose of 10 plants and 20 gy is 29 cm, while the plant height is lowest at a dose of 40 gy is 24 cm. The highest number of shoots was shown by a dose of 50 gy, gy that radiation dose 10 purplish pink flowers and red. Irradiated interest is soaring upwards but then widened to the side.